Coronary Heart Disease, Peripheral Arterial Disease, and Stroke in Familial Hypercholesterolaemia: Insights From the SAFEHEART Registry (Spanish Familial Hypercholesterolaemia Cohort Study). Issue 9 (September 2016) - Pérez de Isla, Leopoldo; Alonso, Rodrigo; Mata, Nelva; Saltijeral, Adriana; Muñiz, Ovidio; Rubio-Marin, Patricia; Diaz-Diaz, José L.; Fuentes, Francisco; de Andrés, Raimundo; Zambón, Daniel; Galiana, Jesús; Piedecausa, Mar; et al.
Abstract : Objective—: Heterozygous familial hypercholesterolemia (FH) is the most common premature atherosclerotic cardiovascular disease (ASCVD)–related monogenic disorder, and it is associated with ischemic heart disease. There is limited information whether FH increases the risk of peripheral arterial and cerebrovascular disease. Our aim was to analyze ASCVD prevalence and characteristics in different arterial territories in a large FH population, to compare them with an unaffected control population and to determine which factors are associated to ASCVD. Approach and Results—: SAFEHEART (Spanish Familial Hypercholesterolaemia Cohort Study) is an ongoing registry of molecularly defined patients with heterozygous FH in Spain. ASCVD in the different arterial territories was analyzed, as well as individual characteristics, genetic variables, and lipid-lowering therapies. The study recruited 4132 subjects (3745 ≥18 years); 2, 752 of those enrolled were molecularly diagnosed FH cases. Median age was 44.0 years (45.9% men) and 40 years (46.6% men) in FH patients and unaffected relatives ( P <0.001). ASCVD was present in 358 (13.0%) and 47 (4.7%) FH patients and unaffected relatives, respectively ( P <0.001). History of premature ASCVD was more prevalent in FH patients (9.4% and 2.4% in FH patients and unaffected relatives, respectively; P <0.001). Coronary artery–related manifestations and peripheral artery disease were more prevalent in FH patients than in controls, but no significant differences were found for cerebrovascular events. Age, body mass index, type 2 diabetes mellitus, high blood pressure, previous use of tobacco, and lipoprotein(a) >50 mg/dL were independently associated with ASCVD. Conclusions—: The prevalence of ASCVD is higher, and the involvement of the arterial territories is different in FH patients when compared with their unaffected relatives. Age, male sex, increased body mass index, hypertension, type 2 diabetes mellitus, smoking habit, and lipoprotein(a) >50 mg/dL were independently associated to ASCVD. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02693548. Abstract : Supplemental Digital Content is available in the text.